MENGEMBANGKAN PSYCHOLOGICAL STRENGTH PESERTA DIDIK MELALUI BIMBINGAN DAN KONSELING - Nursyamsi syamsi (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
is a direct advice to facilitate learners to overcome problems they encounter, and enable them to take the best decision for themselves with full of responsibility. Concept of psychological strength presented in this paper is promoted by Cavanagh (1982). Theorists contend that psychological strength constitutes the power to generate an individual to act in all sphere of his life. The concept of psychological strength consists of three dimensions including: need fulfillment, intrapersonal competencies, and interpersonal competencies. Seffen (2009) defines psychological strength as one’s personal quality that is reflected in his ability to respect himself and other people in life, including the ability to make good relationship with friends, family, and other person, together with the ability to carry out interpersonal communication. This personal power can be developed in the process of individual counseling.Copyright © 2013 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v20i2.35